Developing preservice science teachers’ beliefs about new approaches to science education - Martın Gamez, Carolina; Prıeto Ruz, Teresa; Jımelez Lopez, Mª Angeles (Journal of Turkish Science Education, 2016)
Science education has to take responsibility, and also the challenge, to include comprehensive perspectives that address a number of aspects of very different nature. In this sense, teachers’ beliefs take an important role, given the influence of their actions in the classroom. In this paper, we have researched about the beliefs of a group of pre-service science teachers about new approaches to science education and how such beliefs influenced the reflective process that took place in the activities performed to change those beliefs. The study was carried out in the University of Malaga (Spain), in the fields of “Biology and Geology” and “Physics and Chemistry”. The results and conclusions, which have been obtained by applying a qualitative data analysis methodology, contribute to understand that there are beliefs, with common characteristics, that present a great resistance to change and how certain methodological processes, based on reflection and confrontation of ideas, help to bring certain beliefs near to more innovative approaches.